A toy model of food production in a connected landscape - O'Hare, Anthony (Frontiers in Applied Mathematics and Statistics, 2023)
The drive to maximise food production in a sustainable manner is a paramount concern for farmers and governments. The aim of food producers is to maximise their production yield employing actions such as application of fertiliser or pesticide they believe help to achieve this aim. However, farms do not exist in isolation, but rather share a landscape with neighbours forming networks where any action taken by any one farmer affects their neighbours who are forced to take mitigating actions creating a complicated set of interactions. Understanding these [non-]cooperative interactions and their effect on the shared ecosystem is important to develop food security strategies while protecting the environment and allowing farmers to make a living. We introduce a simple competitive agent based model in which agents produce food that is sold at a fixed price (we ignore market dynamics and do not include explicit punishment on any agent). We analysed agent’s profits in several simple scenarios allowing us to identify the most advantageous set of actions for maximising the yield (and thus profit) for each farmer. We show that the effect of the structure of the network on each farm has implications on the actions taken by agents. These results have implications for the understanding of the effects of farming practices on the environment and how different levels of cooperation between farmers, taking into account the local terrain, can be used to incentivise producers to minimise the effects on the environment while maximising yields.